A pilot study of a Mediterranean-type diet intervention in female patients with rheumatoid arthritis living in areas of social deprivation in Glasgow. Issue 9 (5th July 2007) - McKellar, G; Morrison, E; McEntegart, A; Hampson, R; Tierney, A; Mackle, G; Scoular, J; Scott, J A; Capell, H A
Abstract : Background: A Mediterranean-type diet rich in fish, fruit and vegetables and low in saturated fats has been associated with health benefits, including improved cardiovascular profile and benefit in RA. Objective: To overcome obstacles to healthy eating by a community-based intervention promoting a Mediterranean-type diet in patients with RA living in socially deprived areas of Glasgow. Methods: 130 female patients with RA aged 30–70 years (median 55), disease duration 8 years were recruited from three hospital sites. The intervention group (n = 75) attended weekly 2-hour sessions for 6 weeks in the local community, including hands-on cooking classes backed up with written information. The control group (n = 55) were given dietary written information only. Both groups completed food frequency questionnaires (FFQs), and clinical and laboratory measures were assessed at baseline, 3 and 6 months. Results: Significant benefit was shown in the intervention group compared with controls for patient global assessment at 6 months (p = 0.002), pain score at 3 and 6 months (p = 0.011 and 0.049), early morning stiffness at 6 months (p = 0.041) and Health Assessment Questionnaire score at 3 months (p = 0.03). Analysis of the FFQs showed significant increases in weekly total fruit, vegetable and legume consumption and improvement in the ratio of monounsaturated:saturated fat intake and systolic BP in the intervention group only. The cooking classes were positively received by patients and tutors; cost/patient for the 6 week course was £84 (€124). Conclusions: Results demonstrate that a 6 week intervention can improve consumption of healthier foods. If implemented more widely it may prove a popular, inexpensive and useful adjunct to other RA treatment.